2015
DOI: 10.1007/s00128-015-1467-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of Native Plants for the Remediation of Abandoned Mine Sites in Mediterranean Semiarid Environments

Abstract: Abandoned tailing dumps from mining industry represent important sources of metal contamination in the surrounding environments. This study evaluates the potential of two Mediterranean native plants, Pistacia lentiscus and Phragmites australis, for phytoremediation of two Sardinian contaminated mine sites. A 6 months study has been conducted at greenhouse-controlled conditions with the aim of investigating the plant capability to tolerate high metal concentrations and to extract or immobilize them within the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 30 publications
11
62
1
2
Order By: Relevance
“…Zinc is the most abundant metal in the bulk soils (24,900 CP -32,700 OCP mg/kg), rhizospheres (26,300 CP -27,300 OCP mg/kg) and in the plant tissues (890 OCP -3290 CP mg/kg), followed by Pb (1240 OCP -5000 CP mg/kg in the soils, 1600 OCP -5030 CP mg/kg in the rhizospheres, and 50 OCP -1020 CP mg/kg in the plant tissues) and Cd (100 CP -340 OCP mg/kg in the soils, 170 CP -280 OCP mg/kg in the rhizospheres, and 13 OCP -31 OCP mg/kg in the plant tissues). It should be noted that metal contents detected in this work are of the same order of magnitude as in previous studies [39,41,46,91], in which relevant local variations due to heterogeneities of the mine tailings can be highlighted. [92] 1208 954 BCF, BAC, and TF (Table 3) were calculated to investigate the transfer of metals from geosphere to plant tissues and their translocation from the roots to the epigean organs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Zinc is the most abundant metal in the bulk soils (24,900 CP -32,700 OCP mg/kg), rhizospheres (26,300 CP -27,300 OCP mg/kg) and in the plant tissues (890 OCP -3290 CP mg/kg), followed by Pb (1240 OCP -5000 CP mg/kg in the soils, 1600 OCP -5030 CP mg/kg in the rhizospheres, and 50 OCP -1020 CP mg/kg in the plant tissues) and Cd (100 CP -340 OCP mg/kg in the soils, 170 CP -280 OCP mg/kg in the rhizospheres, and 13 OCP -31 OCP mg/kg in the plant tissues). It should be noted that metal contents detected in this work are of the same order of magnitude as in previous studies [39,41,46,91], in which relevant local variations due to heterogeneities of the mine tailings can be highlighted. [92] 1208 954 BCF, BAC, and TF (Table 3) were calculated to investigate the transfer of metals from geosphere to plant tissues and their translocation from the roots to the epigean organs.…”
Section: Discussionsupporting
confidence: 82%
“…The chemical analysis of bulk soils and rhizosphere materials (Table 2) from the mine dump (CP samples) showed that metal contents (Zn 24,900-26,300 mg/kg, Pb 5000-5030 mg/kg, Cd 100-170 mg/kg) are extremely well above the threshold limits imposed by Italian laws (D.lgs. 152/2006 [90]) for sites for industrial use (Zn 1500 mg/kg, Pb 1000 mg/kg, Cd 15 mg/kg), supporting previous works carried out in the same study area and confirming the high Zn, Pb, and Cd contamination [39,41,46,91]. Also values from OCP samples exceed the Italian pollution thresholds probably due to the aeolian dispersion of fine particles from the nearby tailing dump.…”
Section: Metal Content and Mineralogysupporting
confidence: 81%
“…This is the basis of phytostabilization, a type of phytoremediation in which plants are used to stabilize wastes, prevent wind and water soil erosion, limit the leaching of pollutants into groundwater, and immobilize pollutants by means of physical and/or chemical processes (Sinhal et al 2015 ). Importantly, the effectiveness of phytostabilization can be enhanced by the addition to soil of different sorbent materials such as compost, biochar, water treatment residues or others, able to decrease the bioavailability of PTE and improve the soil physico-chemical and biological properties (Bacchetta et al 2015 ; Garau et al 2014 ; Manzano et al 2016 ). Such approach, which is referred to as aided or assisted phytostabilization, has attracted considerable interest in the last decade and studies evaluating its efficacy are constantly growing (e.g., Alvarenga et al 2008 ; Castaldi et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…by a widespread occurrence of vegetation that dominates the streambed morphology, erosional processes and water velocity. The dominant plant species are Phragmites australis and Juncus acutus (Bacchetta et al, 2015), which are both known to accumulate Zn in high concentrations (Bernardini et al, 2016;Caldelas et al, 2011;Mateos-Naranjo et al, 2014;Rycewicz-Borecki et al, 2016). In this study, a tracer-injection approach (Kimball et al, 1994(Kimball et al, , 2002 was combined with spatially detailed synoptic sampling to quantify water discharge and changes in the metal loads through the study reach.…”
mentioning
confidence: 99%